THE UTILIZATION OF CYBER EXTENSION BY FISH FARMER IN KOTO MESJID VILLAGES OF XIII KOTO KAMPAR SUBDISTRICT KAMPAR REGENCY RIAU PROVINCE - Nazhif Arrahman; Zulkarnain '; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February 2017 in Koto Mesjid Village, Kampar Regency, Riau Province. The selection of the location of this research is done deliberately because the village of Koto Mesjid is an area that most of the fish farmers and almost every house has Wi-Fi access so that this village also bears the title of "Digital Village". This research uses qualitative approach. Informants in this research are the fish farmers in the Koto Mesjid village. The Characteristics of the use of cyber extension on fish farmers in the village of Koto Mesjid can be seen from the age of cultivators that is productive age, the level of higher education and the influence of the surrounding environment. The practice of using cyber extension to fish farmers in Koto Mesjid Village is by inter connecting access, internet calling and chatting. Sources of information obtained from several websites, groups and individuals that can be utilized for fish farming. Utilization of cyber extension on fish farmers in the village of Koto Mesjid can be said to be very useful. This can be seen with the existence of cyber extension, fish farmer become very helpful in finding information that can be applied to the aquaculture fishery activities.Key Word: utilization, cyber extention, fish farmer, interconnecting access.